Factors affecting survival in esophageal squamous cell carcinoma: Single-center experience - Abdullah Sakin (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: Squamous cell esophageal cancer (ESCC) is a highly fatal malignancy. This study aims to investigate the factors affecting survival in patients with metastatic and non-metastatic ESCC. METHODS: Between 2008 and 2016, 107 patients with ESCC who were followed up in an oncology clinic were included in the analysis. Patients were grouped based on the stage of disease as clinical-stage II to IV. RESULTS: Of the 107 patients, 55 (55.1%) of them were male and 52 (48.6%) of them were female. The mean age was 60.8 years. Based on the clinical-stage, 28 (26.2%) patients had stage II disease, 33 (30.8%) had stage III disease, and 46 (43.0%) had stage IV disease. Twenty-nine (27.1%) patients with the non-metastatic disease underwent surgery following neoadjuvant chemoradiotherapy (CRT), while 29 (27.1%) patients received definitive CRT. Twenty-six (56.5%) patients with metastatic disease received chemotherapy (CT). While median overall survival (mOS) could not be reached in patients who underwent surgery following neoadjuvant CRT, mOS for patients receiving definitive CRT versus patients treated with surgery alone–was 22.0 months and 24.0 months, respectively (p=0.008). In the metastatic stage, mOS was 8.0 months for the patients treated with a first-line CT and 3.0 months for patients receiving best supportive care (p<0.001). In multivariate analysis, factors predicting survival in patients with the non-metastatic disease were ECOG PS 3-4 (Hazard ratio [HR], 6.13), undergoing surgery (HR, 0.22), clinical-stage III disease (HR, 3.19), and presence of recurrence (HR, 24.12). For patients with metastatic disease, ECOG PS 3-4 (HR, 3.31), grade-III histology (HR, 3.39), liver metastasis (HR, 2.53), and receiving CT (HR, 0.15) were the factors associated with survival in multivariate analysis. CONCLUSION: In our study, surgery and early clinical-stage increased survival, whereas experiencing recurrence adversely affected survival in non-metastatic ESCC. In the metastatic stage, ECOG PS 3-4, grade-3 histology and liver metastasis adversely affected survival, while receiving CT significantly improved survival.